1967
DOI: 10.1079/bjn19670010
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and stress

Abstract: I. A critical analysis of the biological antioxidant theory of vitamin E function has been made and the implications of the theory have been tested.2. When small amounts of [5-Me-'*C]a-tocopherol were present in lipid systems subject to autoxidation in vitro, it was found that, whether the tocopherol was the sole antioxidant or was in synergistic combination with a secondary antioxidant (ascorbic acid), peroxidation did not occur without concomitant destruction of the tocopherol. This was so, whether a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 104 publications
3
40
0
Order By: Relevance
“…Diplock, 1976). Further, the studies by Little & O'Brien (1968) showed that lipid peroxides are substrates for this enzyme. Nevertheless, the fact that the rate of destruction of trace quantities of a-[W4C]tocopherol in the tissues of vitamin E-deficient animals is not increased by dietary polyunsaturated fatty acids (Green et al, 1967) indicates that the nutritional interaction between a-tocopherol and unsaturated lipids cannot be ascribed solely to an antioxidant mechanism. On the basis of molecular-model building, it was there-fore proposed that a-tocopherol may physically stabilize biological membranes that are rich in polyunsaturated phospholipids: this stabilization might arise from interactions between the phytyl side chain of a-tocopherol and the polyunsaturated fatty acyl residues of phospholipid molecules in the hydrophobic regions of biological membranes (Lucy, 1972;Diplock & Lucy, 1973).…”
mentioning
confidence: 99%
“…Diplock, 1976). Further, the studies by Little & O'Brien (1968) showed that lipid peroxides are substrates for this enzyme. Nevertheless, the fact that the rate of destruction of trace quantities of a-[W4C]tocopherol in the tissues of vitamin E-deficient animals is not increased by dietary polyunsaturated fatty acids (Green et al, 1967) indicates that the nutritional interaction between a-tocopherol and unsaturated lipids cannot be ascribed solely to an antioxidant mechanism. On the basis of molecular-model building, it was there-fore proposed that a-tocopherol may physically stabilize biological membranes that are rich in polyunsaturated phospholipids: this stabilization might arise from interactions between the phytyl side chain of a-tocopherol and the polyunsaturated fatty acyl residues of phospholipid molecules in the hydrophobic regions of biological membranes (Lucy, 1972;Diplock & Lucy, 1973).…”
mentioning
confidence: 99%
“…If a-tocopherol functions in the manner that we have suggested (Diplock & Lucy, 1973) to form a physicochemical interaction between its side chain and arachidonyl moieties of membrane phospholipids, then oxidative destruction of atocopherol (as suggested by McCay etal., 1971) might not necessarily occur, since the antioxidant (hydroxyl) function of tocopherol need not be involved. The failure of Green et al (1967) to demonstrate increased destruction of small amounts of 14C-labelled atocopherol in vitamin E-deficient rats given large amounts of dietary polyunsaturated fatty acids might thus be explained. Further, the possibility of accelerated breakdown of membrane-associated phospholipids by endogenous phospholipases must be considered; the expected alteration in the membrane architecture in vitamin E deficiency would be expected to lead to an increased accessibility of the substrate, polyunsaturated fatty acyl residues of membrane phospholipids, to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…If a-tocopherol functions in the manner we have suggested (Diplock & Lucy, 1973) to promote membrane stability and compactness by physical means, then destruction of or-tocopherol might not be seen as a corollary of peroxidative attack on unsaturated fatty acids. This could thus explain the failure of Green, Diplock, Bunyan, McHale & Muthy (1967) to demonstrate an increased rate of destruction of 14C-labelled a-tocopherol in rats given large amounts of PUFA. Furthermore, the possibility of accelerated breakdown of membrane-associated phospholipids by endogenous phospholipases in the absence of tocopherols must be considered (Diplock & Lucy, 1973).…”
Section: (3)mentioning
confidence: 99%
“…I n a critical and detailed study of the antioxidant hypothesis, Green and co-workers (e.g. Green, Diplock, Bunyan, McHale & Muthy, 1967 ;Green, Diplock, Bunyan, Muthy & McHale, 1967) could find little evidence that PUFA-exacerbated vitamin E deficiency was accompanied by increased destruction of I4C-labelled a-tocopherol, or by accumulation of lipid peroxides, the two criteria that had come to be regarded as implicit in the hypothesis. I n a review of this work, Green & Runyan (1969) concluded that the results were 'contrary to the requirements of the theory'.…”
Section: Introductionmentioning
confidence: 99%